BUDAYA HEDONISME DI KALANGAN LGBT (ANALISIS WACANA KRITIS N. FAIRCLOUGH PADA PODCAST DEDDY CORBUZIER EPISODE LUCINTA LUNA) - Virgiawan, Josephine; Amalia, Dinda Nur; Fathoni, Khusnul (Universitas 17 Agustus 1945 Surabaya, 2024)
The world of the entertainment industry has now become a forum that can play an inclusive role in accommodating various things, especially for LGBT (Lesbian, Gay, Bisexual, and Transgender) groups to enable them to be more open in expressing themselves and dare to be exposed in sharing their activities and lives. personal, as well as their daily lives on social media. One of the phenomena that highlights this dynamic was based on a podcast broadcast on a YouTube channel owned by an artist named Deddy Corbuzier who guest star Lucinta Luna, a transgender celebrity who has caused a lot of controversy in Indonesia. This research examines how the implementation and development of the culture of hedonism is discussed, especially by one of the marginalized groups in Indonesia, such as the LGBT group. The method used in this study is a qualitative approach. It uses Norman Fairclough's Critical Discourse Analysis Theory, which examines the structure of language or text, discursive practices, and the socio-cultural context behind a discourse that is echoed. The results of this research show that Lucinta Luna as a subject who represents the LGBT group in her presentation uses language that can be said to be blunt, very open, invites a variety of opinions, and makes the watching audience have a different perspective when describing the needs and lifestyle of hedonism as well as the power he obtained and exercised from the controversial wealth resulting from being a transgender person, especially in Indonesia. This is a reflection of other LGBT people, who are starting to dare to promote the culture of hedonism as a necessity to achieve fame and success for LGBT groups. These findings provide a new understanding of the discourse practices of marginalized LGBT groups in Indonesia and critical discourse studies in a digital context. Keywords: Hedonistic Culture, LGBT, Critical Discourse Analysis, Group